Scarlet A : the ethics, law, and politics of ordinary abortion - Watson, Katie (Oxford University Press, 2018)
Although Roe v. Wade identified abortion as a constitutional right 45 years ago, it still bears stigma - a proverbial scarlet A. Millions of Americans have participated in or benefited from an abortion, but few want to reveal that they have done so. Approximately one in five pregnancies in the US ends in abortion. Why is something so common, which has been legal so long, still a source of shame and secrecy? Why is it so regularly debated by politicians, and so seldom divulged from friend to friend? This book explores the personal stigma that prevents many from sharing their abortion experiences with friends and family in private conversation, and the structural stigma that keeps it that way.